IMPLEMENTATION OF PELAKU PARA DEWI TO IMPROVE GOVERNMENT SERVICES IN TANJANGRONO VILLAGE - Rokmahwati, Pungki; Mursyidah, Lailul (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the implementation of Pelaku Para Dewi, a digital innovation in population administration services, and its impact on improving the quality of government services in Tanjangrono Village, Mojokerto Regency. Method: Employing a qualitative approach with purposive sampling, data were collected through observation, interviews, and documentation, and analyzed using the Van Meter and Van Horn policy implementation model, which evaluates policy objectives, resources, implementers’ characteristics, and inter-organizational communication. Results: The findings reveal that Pelaku Para Dewi has significantly improved service efficiency and accessibility, with residents reporting convenience and enhanced data security as key benefits. The successful implementation was supported by trained operators and adequate infrastructure, although challenges persist in community socialization and limited digital literacy. Novelty: As the first empirical study to examine Pelaku Para Dewi at the village level, this research contributes new insights into rural digital service delivery in Indonesia and offers a valuable reference for formulating digitalization strategies in public service management, particularly in addressing local needs and fostering inclusive governance.